Penyusunan Authentic Assessment Dengan Pendakatan Intercultural Communicative Comptence Bagi Pengajar Bahasa Inggris Yayasan SAS ANA - Ahmad Laut Hasibuan; Nazriani Lubis; Asnarni Lubis; Putri Regina; Sania Diva Maharani; Gabriel Mardin Gokma Simangunsong (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Authentic Assessment with the Intercultural Communicative Competence (ICC) approach offers comprehensive and thorough evaluations so that students can receive significant feedback. However, the implementation of Authentic Assessment with the ICC approach is still rarely carried out by English teachers at Yayasan SAS ANA Group because the teachers still use conventional assessments. This community service activity aims to enhance the understanding of English tutors in implementing Authentic Assessment with the ICC approach in English teaching. carried out systematically through the following stages: socialization, initial questionnaire completion, delivery of material using a communicative and tutorial approach, assessment creation practice, small group discussions, and continuous evaluation and mentoring. The survey results indicate a significant improvement in their understanding related to planning, interpretation, application, performance, and evaluation of assessments using the ICC approach